Character education as a mediator in the formation of morality in schools - Purnama Syae Purrohman; Ahmad Ruslan; Herdin Muhtarom; Rafli Pasila Nasmu (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
This study analyzes the role of digitalization in preserving and accessing local and national history in the era of globalization. The issues examined include national challenges related to national identity and cultural diversity. The objective of this research is to evaluate character ducation as a mediator in the formation of morality in schools. The methods is qualitative that related used include literature analysis, case studies, as well as surveys and interviews with relevant stakeholders. Data were collected from digital archives, official websites, and social media platforms. The findings indicate that This approach allows students not only to conceptually understand character values ​​but also to practice them in real life. Teachers act as primary role models who reinforce the internalization of values ​​such as honesty, discipline, responsibility, empathy, and cooperation, while a conducive school environment supports the growth of students' sense of security, self-confidence, and motivation to learn. This research shows that character education implemented holistically, consistently, and collaboratively involving schools, families, and the social environment has a significant influence on the formation of students' morality. With this approach, students are expected to grow into a generation that is not only intellectually intelligent, but also has strong character, good morals, and is ready to contribute positively to social life, both in the real world and in the increasingly complex digital era.